2016
DOI: 10.1016/j.ijpharm.2016.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Functional physico-chemical, ex vivo permeation and cell viability characterization of omeprazole loaded buccal films for paediatric drug delivery

Abstract: 25Buccal films were prepared from aqueous and ethanolic Metolose gels using the solvent casting approach (40°C). The hydration (PBS and simulated saliva), mucoadhesion, physical stability (20°C, 40°C), in vitro drug (omeprazole) dissolution (PBS and simulated saliva), ex vivo permeation (pig buccal mucosa) in presence of simulated saliva, ex vivo bioadhesion and cell viability using MTT of drug loaded (DL) films were investigated. Hydration and mucoadhesion 30 results showed that swelling capacity and adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…In figure 4 c it can be observed that the MET:CAR 1:1 and 3:1 wafers (samples B1, B2, C1 and C2) had longer swelling duration of about 120 minutes and lower swelling capacity which is due to the higher concentrations of MET which act as a stabilizer for the wafers (Shin Etsu Chemical, 2005). In SS the swelling profile of MET:CAR 3:1,1:1 and 1:3 (samples A1, B1, C1, A2, B2 and C2) were lower than when performed in PBS (Figure 4d) which could be due to the difference in ionic strength of the media and that plays an important role in the swelling of the wafers (Khan, et al, 2016).…”
Section: Swelling Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…In figure 4 c it can be observed that the MET:CAR 1:1 and 3:1 wafers (samples B1, B2, C1 and C2) had longer swelling duration of about 120 minutes and lower swelling capacity which is due to the higher concentrations of MET which act as a stabilizer for the wafers (Shin Etsu Chemical, 2005). In SS the swelling profile of MET:CAR 3:1,1:1 and 1:3 (samples A1, B1, C1, A2, B2 and C2) were lower than when performed in PBS (Figure 4d) which could be due to the difference in ionic strength of the media and that plays an important role in the swelling of the wafers (Khan, et al, 2016).…”
Section: Swelling Studiesmentioning
confidence: 88%
“…MET is a non-ionic cellulose ether composed of methylcellulose and three types of HPMC which are available in different grades with varying viscosities. The most important properties of MET includes solubility in cold water, development of transparent solutions and viscoelastic properties (Khan, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its stability in aqueous solution is entirely dependent on the initial pH and, it is rapidly degraded in acidic and neutral conditions but shows greater stability in alkaline medium. We have previously shown the potential of OME based buccal films for sustained delivery of via the buccal mucosa for paediatric administration (Khan et al, 2015) and demonstrated the release and permeation of the drug 4 across pig buccal membrane (Khan et al, 2016). However, though OME is well absorbed from the gastrointestinal tract its oral bioavailability in humans of about 50% which suggests first pass metabolism for this drug.…”
Section: Methyl] Sulfinyl]-1h-benzimidazole)mentioning
confidence: 99%
“…In previous studies (Khan et al, 2015(Khan et al, , 2016, we developed mucoadhesive and sustained release MET based films incorporating OME as a model drug and L-arg as stabilising agent to prevent drug degradation. Functional characterisation showed release of the drug and subsequent permeation through pig buccal tissues over a two hour period, owing to prolonged retention at the buccal mucosa surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation